How power relationships are involved in research methods - Bandsma, Koen; Greinke, Lena; MacCarthy, Danielle (AESOP, 2019)
With the rise of activism and activist research, this paper explores how power relationships are involved in traditional and emerging methods used in research on activism. This question matters as research methods have the potential to both improve the capacities of activist groups and enhance knowledge of agents involved: researcher and activist. The added value of the paper is that it presents a range of methods used in research on activism, including new methods that are relatively uncommon in planning research. The second contribution of this paper is that it is based on a power framework by Forester; it analyses how power is embedded in the use of a particular research method. The authors find extant differences between the methodologies when analyzed through this framework, especially in their potential to involve with activist communities. The authors encourage researchers to be braver in using activist research methods and to be aware of the underlying power discourses in their choices.
plaNext-Next Generation Planning Vol. 8 (2019) : Making space for hope 21-31